Phylogenetic and systematic studies of the amorphophallus species in Sarawak - Aizat, Japar (Universiti Malaysia Sarawak (UNIMAS), 2013)
A systematic study was conducted on ten species of Amorphophallus in Sarawak based on morphology, ecology and genomic sequences data. The objectives of this study were; (I) to document morphological characteristics and ecological data of ten selected Amorphophallus species in Sarawak; (2) to find a suitable method of DNA extraction (3) to reconstruct phylogenetic tree and examine the phylogenetic relationship between the Amorphophallus speciej) Materials to be used as herbarium specimen and DNA samples were collected, from localities around Sarawak such as Kuching, Sri Aman, Padawan and Mulu. Random amplified polymorphic DNA technique was applied and genetic profiles were obtained for the selected species generated using primers OPC-06, OPD-05 and OPD-20. Dendrogram created using the unweighted pair group method with arithmetic averages provide enough information for the analysis of genetic diversity. Phylogenetic trees for Amorphophallus species were reconstructed using two genomic sequence, rbcL genes and trnL-F intergenic spacer. The sequenced data was analyzed by four different methods; Bayesian, maximum likelihood, maximum parsimony and neighbor joining. The out-groups for the phylogenetic trees are from genus Arisaema, DiefJenbachia, and Bognera. The reconstructed phylogenetic trees were successful to resolve phylogenetic relationship for several species ofAmorphophallus.